Prolonged NHE Activation may be both Cause and Outcome of Cytokine Release Syndrome in COVID-19 - Cure, Medine C.; Cure, Erkan (Current Pharmaceutical Design, 2022)
The release of cytokines and chemokines such as IL128;1β, IL-2, IL-6, IL-7, IL-10, TNF-α, IFN128;γ, CCL2, CCL3, and CXCL10 is increased in critically ill patients with COVID-19. Excessive cytokine release during COVID-19 is related to increased morbidity and mortality. Several mechanisms are put forward for cytokine release syndrome during COVID-19. Here we have mentioned novel pathways. SARS-CoV-2 increases angiotensin II levels by rendering ACE2 nonfunctional. Angiotensin II causes cytokine release via AT1 and AT2 receptors. Moreover, angiotensin II potently stimulates the Na+/H+ exchanger (NHE). It is a pump found in the membranes of many cells that pumps Na+ inward and H+ outward. NHE has nine isoforms. NHE1 is the most common isoform found in endothelial cells and many cells. NHE is involved in keeping the intracellular pH within physiological limits. When the intracellular pH is acidic, NHE is activated, bringing the intracellular pH to physiological levels, ending its activity. Sustained NHE activity is highly pathological and causes many problems. Prolonged NHE activation in COVID-19 may cause a decrease in intracellular pH through H+ ion accumulation in the extracellular area and subsequent redox reactions. The activation reduces the intracellular K+ concentration and leads to Na+ and Ca2+ overload. Increased ROS can cause intense cytokine release by stimulating NF-ΚB and NLRP3 inflammasomes. Cytokines also cause overstimulation of NHE. As the intracellular pH decreases, SARS-CoV-2 rapidly infects new cells, increasing the viral load. This vicious circle increases morbidity and mortality in patients with COVID-19. On the other hand, SARS-CoV-2 interaction with NHE3 in intestinal tissue is different from other tissues. SARS-CoV-2 can trigger CRS via NHE3 inhibition by disrupting the intestinal microbiota. This review aimed to help develop new treatment models against SARS-CoV-2- induced CRS by revealing the possible effects of SARS-CoV-2 on the NHE.
Keywords: COVID-19